A Goal-Directed Bayesian Framework for Categorization - Rigoli, Francesco; Pezzulo, Giovanni; Dolan, Raymond; Friston, Karl (Frontiers in Psychology, 2017)
Categorization is a fundamental ability for efficient behavioural control. It allows organisms to remember the correct responses to categorical cues and not for every stimulus encountered (hence eluding computational cost or complexity), and to generalize appropriate responses to novel stimuli dependant on category assignment. Assuming the brain performs Bayesian inference, based on a generative model of the external world and future goals, we propose a computational model of categorization in which important properties emerge. These properties comprise the ability to infer latent causes of sensory experience, a hierarchical organization of latent causes, and an explicit inclusion of context and action representations. Crucially, these aspects derive from considering the environmental statistics that are relevant to achieve goals, and from the fundamental Bayesian principle that any generative model should be preferred over alternative models based on an accuracy-complexity trade-off. Our account is a step towards elucidating computational principles of categorization and its role within the Bayesian brain hypothesis.